Transport durable et développement économique - Corinne Meunier; Thomas Zéroual (Développement Durable et Territoires)
Transportation generates negative externalities (especially environmental ones) widely known and denounced. Thereby, the reference to sustainability, now incontrovertible in many areas of the public action, reaches transportation via the concept of sustainable transportation. The most important need in sustainability is on freight transportation : carriage growth rate is higher than passenger transportation, and the unevenness between the modal parts is in favour of the most polluting. On freight transportation, the European Union policy exercises a determining opinion, both on the French public policies (at every scale) and on most of the actors stepping in the transportation domain in France. The topic of this paper is on the segment of carriage flux and on the European translation of the founding principles of sustainable transportation.